Development and Validation of Zerumbone Analysis Method Using Ultraviolet-Visible Spectrophotometry - Doloking, Haeria; Muhlisuddin, Muhlisuddin; Maddeppungeng, Nurul Muhlisah (Universitas Jenderal Soedirman, 2025)
ABSTRACT. Analytical method development ensures that an analytical procedure is suitable for the identification and quantification of compounds of interest. This study aimed to develop and validate a simple, cost-effective analytical method for the determination of zerumbone using UV-Vis spectrophotometry. Method validation was conducted according to ICH Q2(R2) guidelines, including tests for specificity, linearity, limit of detection (LOD), limit of quantification (LOQ), accuracy, and precision. Zerumbone exhibited a maximum absorption wavelength (λmax) of 212 nm when dissolved in dimethyl sulfoxide (DMSO). The method demonstrated excellent linearity with a determination coefficient (R2) of 0.9991 across a concentration range of 10-50 μg/mL. Accuracy, evaluated via recovery studies, ranged from 91,00% to 110,45%. Precision testing results in a % RSD of 0.58%. The calculated LOD and LOQ were 1.55 μg/mL and 4.70 μg/mL, respectively. This validated method is simple, rapid, and economical, making it a promising alternative for zerumbone analysis in quality control laboratories. Keywords: Zerumbone, Method Development, UV-Vis Spectrophotometry, Validation, ICH Guidelines.